2022
DOI: 10.3390/antiox11091674
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Anthocyanins Ameliorate DSS-Induced Ulcerative Colitis by Improving Intestinal Barrier Function and Modulating Gut Microbiota

Abstract: Mulberry has attracted wide attention due to its substantial nutritional values. This work first studied the protective effect of mulberry anthocyanins (MAS) on dextran sulfate sodium (DSS)-induced colitis. The mice experiment was designed as four groups including normal mice (Control), dextran sodium sulfate (DSS)-fed mice, and DSS plus 100 mg/kg·bw MAS-fed mice (LMAS-DSS) or DSS plus 200 mg/kg·bw MAS-fed mice (HMAS-DSS). Mice were given MAS by gavage for 1 week, and then DSS was added to the drinking water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 62 publications
4
25
1
Order By: Relevance
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies [77][78][79][80][81] . According to certain research articles, the Fir/Bac ratio is a defining characteristic of obesity.…”
Section: Discussionsupporting
confidence: 83%
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies [77][78][79][80][81] . According to certain research articles, the Fir/Bac ratio is a defining characteristic of obesity.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, Bacteroidetes had the highest relative abundance and occupied the main part of all flora, and had an important role in restoring the gut barrier and modulating inflammation. [ 50 ] The relative abundance of Bacteroidetes decreased in the IBD but increased significantly after TACS treatment. Compared with the healthy, the operational taxonomic unit (OTU) richness and α ‐diversity (Simpson and Shannon Index) were not changed in the other groups (Figure S43A–C, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have highlighted the potential protective role of genus Akkermansia against colitis. Specifically, Akkermansia muciniphila, a resident of the human gut, has been observed to have beneficial effects on the intestinal barrier function and inflammatory responses. , It is pertinent to mention that certain botanical extracts have shown to increase the abundance of this particular bacteria, fortifying the gut barrier and potentially ameliorating symptoms of IBD. , Although our study witnessed a rise in the Duncaniella genus, future research could delve into the potential synergies or complementary impacts of Virofree on other advantageous genera, such as Akkermansia.…”
Section: Discussionmentioning
confidence: 81%